Phenocam - Green Chromatic Coordinates (GCC) Composite Image Mean Values from Nybygget, Mast 7.25m Phenocam 01 - Asa Research Station (Swedish University of Agricultural Sciences, 2022)
Green Chromatic Index (GCI) also known as Green Chromatic Coordinate (GCC) is a measure of the greenness of vegetation.  It is calculated from daily averaged RGB (Red, Green, Blue) composites values of digital images captured by PhenoCams.
Asa Research Station (2022). Phenocam - Green Chromatic Coordinates (GCC) Composite Image Mean Values from Nybygget, Mast 7.25m Phenocam 01, 2017-01-01–2017-12-31 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/0JDr8TQzBUpkaBIiSN0wrHCb
Keywords: SITES Spectral; Calibration/Validation; Ecosystem functions; Plant Phenology; Reflectance; Vegetation Index; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap